USO DO MEL COMO AGENTE DE CARBONATAÇÃO: EFEITOS NAS PROPRIEDADES QUÍMICAS DE CERVEJAS ARTESANAIS - Giacomazzi Zucco, Isadora; Victor Piassa, Beatriz; de Paula Arantes, Otávio; Millena de Freita, Cristhyane; Pelegrini Roviero, Juliana (Intercursos, 2026)
não há